Caracterização e utilização de biomassa de banana verde e farinha de sorgo na produção e avaliação sensorial de bananadas - Aline Cristina Pinheiro Amorim de Melo (2019)
Although flavor is considered a strong factor influencing food choices, consumers are increasingly concerned about healthier food choices. In general, they consider not only calories but also health information as an important parameter for choosing foods. In order to meet this demand, bananas were produced with ingredients containing starch resistant (RS). The ingredients added to the banana were biomass of green banana and sorghum flour rich in this component. The main objective of this thesis was to characterize the biomass of green banana and sorghum flour in the production and sensory evaluation of banana plants. To obtain biomass of the green banana, the thermal processing time for the biomass extraction with the maximum retention of the RA was investigated. The results demonstrated that the time of 12 minutes at 121 ° C is the ideal processing condition of the green banana for the maximum RA retention, less than 20 minutes, as recommended in the literature, which drastically reduces the RA content of biomass of the green banana. The formulations developed were sensorially tested. The blind and informed acceptance tests were applied to 120 testers in 2 sessions, in addition to the CATA, Healthyness and Willingness to Pay (WTP) descriptive test. In the evaluation by descriptors, 23 of the 29 terms originally employed were selected after the Cochran Q test. In the acceptance test, the samples presented a good performance, since all presented notes in the area of acceptance